Event-triggered input-to-state stabilization of nonlinear systems subject to disturbances and dynamic uncertainties - Liu, Tengfei; Zhang, Pengpeng; Jiang, Zhong-Ping (Automatica (Oxford), 2019)
This paper studies the design of event-triggered control schemes for nonlinear systems subject to both external disturbances and dynamic uncertainties. To avoid Zeno behavior, this paper proposes an event-triggering mechanism (ETM) that uses not only the measured system state but also an estimation of the influence of the external disturbances and dynamic uncertainty. It is shown that the proposed ETM guarantees that the inter-sampling intervals are bounded below by a positive constant, leading to the absence of Zeno phenomenon. Moreover, the closed-loop event-triggered system is input-to-state stable (ISS) with the external disturbance as the input. Nonlinear small-gain tools are refined for stability analysis.